1995
DOI: 10.1074/jbc.270.32.18715
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Poly(ADP-ribose) Polymerase by Interleukin-1β Converting Enzyme and Its Homologs TX and Nedd-2

Abstract: The proteolytic cleavage of poly(ADP-ribose) polymerase (PARP) is an early biochemical event, which occurs during apoptosis. A recent study suggested that PARP cleavage can be mediated by a novel cytosolic protease (prICE) that resembles interleukin-1 beta converting enzyme (ICE), but cannot be mediated by ICE itself (Lazebnik, Y.A., Kaufmann, S.H., Desnoyers, S., Poirier, G.G., and Earnshaw, W.C. (1994) Nature 371, 346-347). We have used a COS cell co-transfection assay to investigate if ICE or any known ICE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(102 citation statements)
references
References 22 publications
6
95
1
Order By: Relevance
“…In addition, this proteolytic cleavage decreases the activity of PARP and the 85-kDa fragment retains only basal PARP activity. The ICElike cysteine proteases are the executors for this PARP cleavage (Gu et al, 1995). However, in this study, the apparent PARP cleavage during the course of apoptosis is not observed, suggesting that ICE-like cysteine protease is not involved in GL331-mediated cell death.…”
Section: Figurecontrasting
confidence: 63%
“…In addition, this proteolytic cleavage decreases the activity of PARP and the 85-kDa fragment retains only basal PARP activity. The ICElike cysteine proteases are the executors for this PARP cleavage (Gu et al, 1995). However, in this study, the apparent PARP cleavage during the course of apoptosis is not observed, suggesting that ICE-like cysteine protease is not involved in GL331-mediated cell death.…”
Section: Figurecontrasting
confidence: 63%
“…58 PARP was one of the first identified examples of a substrate processed by an executioner caspase much more efficiently than the inflammatory caspase-1. 59,60 The PARP cleavage site perfectly matches the substrate specificity of executioner caspases-3 and -7. Interestingly, secondary interactions seem to be at work because caspase-7, which is less catalytically active than caspase-3 on short synthetic substrates, processes PARP molecules modified with long, branched poly(ADP-ribose) chains more efficiently than its close homolog caspase-3.…”
Section: Gain-of-functionmentioning
confidence: 71%
“…At higher concentrations (3 mg/ml), the PARP cleavage site peptide showed broad spectrum inhibition of all caspases (Table 2). This is reminiscent of the ability of caspases other than caspases-3 and -7/a to cleave PARP, albeit with lower e ciency (Fernandes- Alnemri et al, 1995a;Gu et al, 1995;Duan et al, 1996b;Muzio et al, 1996). The lamin A cleavage site peptide preferentially inhibited F19 and S19, with other caspases showing much lower sensitivities (F19»F20&F174F22; S19»S20&S174S22; Figure 3c, lane 2).…”
Section: Stepwise Activation Of Caspases In Apoptotic Jurkat Cells Rementioning
confidence: 87%